Frekuensi Hubungan Seksual dan KB Pil Kombinasi terhadap Terjadinya Erosi Portio pada Wanita Pasangan Usia Subur - Yusri Dwi Lestari; Siti Nur Farida (Jurnal Kesehatan Manarang, 2021)
Portio erosion is a wound or inflammation of the cervix (portio). Inflammation can be caused by hormonal changes, during pregnancy, contraceptive pill use, installation and removal of IUDs, and lack of personal hygien. This erosion can bleed easily and cause bleeding or metrorrhagia. This study aims to determine the relationship between the frequency of sexual relations and the use of the combined oral contraceptive pill to erosion of portion in reproductive women. This research is an analytic study with a cross sectional design with accidental sampling. Data collection was carried out using interviews and direct observation. Data analysis by a cross tabulation with Spearman Rank test through SPSS software. The results obtained are severe portio erosion covering more than 2/3 of the total cervical area of ​​8 women (53%) based on the frequency of sexual intercourse, and mild portio erosion covers less than 1/3 of the total cervical area of ​​10 women (67%) based on the combined oral contraceptive pill. The study concludes that the frequency of sexual intercourse affected the incidence of portio erosion. The use of the combined oral contraceptive pill has affected the incidence of portio erosion in the POSKESDES Binor Paiton Probolinggo. The results of this study are input for women of childbearing age who are sexually active and use combined pill contraceptives to be more aware of the health of their reproductive organs by routinely performing an IVA or Pap smear at least once a year.